Developing algorithms for estimating total suspended solids (TSS) using unmanned aerial vehicle: A case study in the Upper Citarum River, Indonesia - Fajar Setiawan; Tyas Mutiara Basuki; Budi Heru Santosa; Irfan Budi Pramono; Galdita Aruba Chulafak; Aldiano Rahmadya; Firda Maftukhakh Hilmya Nada (Journal of Degraded and Mining Lands Management)
Monitoring total suspended solids (TSS) is essential as suspended sediments impact the environment and human health in various ways. However, TSS data are limited in many regions because the methods currently applied through in situ measurements are time-consuming and labor-intensive. The study aimed to develop algorithms to estimate TSS using data derived from UAVs and field measurements. Remote sensing technology, such as unmanaged aerial vehicle (UAV), was applied to obtain imagery data to estimate TSS content. These results were then compared with laboratory analysis of in-situ water samples, determined by gravimetric methods following standard protocols. The results showed that the algorithm developed using three-band ratios, the blue/green + red/green + NIR (near infra red)/green, produces a high R2 (0.70), indicating that this combination is reliable for use in estimating TSS content in a river section. The high accuracy of the red band for suspended sediment prediction is attributed to its spectral signature in turbid water, which shows higher reflectance compared to clean water. The results of this study have the potential to help river managers obtain TSS data quickly at a relatively low cost.